Successful amphiphiles as the key to crystallization of membrane proteins: Bridging theory and practice - Breibeck, Joscha; Rompel, Annette (Biochimica et biophysica acta. General subjects, 2019)
Membrane proteins constitute a major group of proteins and are of great significance as pharmaceutical targets, but underrepresented in the Protein Data Bank. Particular reasons are their low expression yields and the constant need for cautious and diligent handling in a sufficiently stable hydrophobic environment substituting for the native membrane. When it comes to protein crystallization, such an environment is often established by detergents. In this review, 475 unique membrane protein X-ray structures from the online data bank “Membrane proteins of known 3D structure” are presented with a focus on the detergents essential for protein crystallization. By systematic analysis of the most successful compounds, including current trends in amphiphile development, we provide general insights for selection and design of detergents for membrane protein crystallization. The most successful detergents share common features, giving rise to favorable protein interactions. The hydrophile-lipophile balance concept of well-balanced hydrophilic and hydrophobic detergent portions is still the key to successful protein crystallization. Although a single detergent compound is sufficient in most cases, sometimes a suitable mixture of detergents has to be found to alter the resulting protein-detergent complex. Protein crystals with a high diffraction limit involve a tight crystal packing generally favored by detergents with shorter alkyl chains. The formation of well-diffracting membrane protein crystals strongly depends on suitable surfactants, usually screened in numerous crystallization trials. The here-presented findings provide basic criteria for the assessment of surfactants within the vast space of potential crystallization conditions for membrane proteins. [Display omitted] •The vapor diffusion technique is still the most prevailing method for membrane protein crystallization.•Crystallization of membrane proteins requires proper selection of detergents.•Dergents can show head-to-tail amphiphilicity or side-to-side (facial) amphiphilicity.•Fundamental detergent properties are based on the HLB concept.•Current trends in development of novel detergent compounds focus on structural rigidification of the detergent molecule.